Analisis Faktor yang Berpengaruh terhadap Motivasi Orangtua pada Pelaksanaan Program Bias - Agustin Nurngafiah; Laurensia Yunita; Angga Irawan (Pusat Riset dan Inovasi Nasional, 2023)
Infectious diseases in infants are one of the causes of high infant mortality. The infectious diseases are hepatitis B, polio, tuberculosis, diphtheria, pertussis, tetanus, and measles. Since 1991, pertussis cases have emerged as a frequently reported case in Indonesia, about 40% of pertussis cases affect toddlers. The purpose of the study was to analyze the factors that influence parental motivation in the implementation of the Bias Program at the Salam Babaris Health Center. Analytical survey research method with cross sectional approach. The sample in this study was 50 mothers. Primary data collection was analyzed using descriptive test and chi square test. The results of the study showed that most respondents had good knowledge as many as 30 people (60%), higher education (SMA / PT) as many as 35 people (70%), age not at risk (20-35 years) as many as 36 people (72%), good parental motivation as many as 21 people (42%). There is an influence of knowledge on parental motivation in the implementation of the Bias program (pvalue: 0.011<0.05). There is an influence of education on parental motivation in the implementation of the Bias program (pvalue: 0.000<0.05). There is an influence of age on parental motivation in the implementation of the Bias program (pvalue: 0.025<0.05).